EFFECT OF COMBINATION THERAPY PROGESSIVE MUSCLE RELAXATION AND CLASSICAL MUSIC ON REDUCING DYSMENORRHEA - Retno Gumelar, Wahyu; Ekawati, Heny; Budya Ningrum, Afita; Setiya Ningsih, Yuli; Amandha Inayatul Hayya, Sylvie Aprilyanti (Universitas Airlangga, 2024)
Introduction: Dysmenorrhea is a pain commonly felt during menstruation in the lower abdomen to the thighs, and the pain lasts for one to several days during menstruation. Dysmenorrhea can affect daily activities if not treated properly. The purpose of this study was to determine the effect of combined therapy of progressive muscle relaxation and classical music on reducing menstrual pain (dysmenorrhea) in junior high school students at SMPN 2 Kedungadem, Bojonegoro District. Methods: This research applied pre-experimental design (one group pre-posttest). The sample was 37 female students who were randomly obtained by using a simple random sampling. The data was gathered through a numerical pain rating scale. Then, it was tabulated and analyzed using Paired T-test. Results: The results showed that there was a significant effect with a value of p=0.000 or p <0.05, meaning that the combination therapy of progressive muscle relaxation and classical music can reduce menstrual pain (dysmenorrhea). Conclusions: It is hoped that the combination therapy of progressive muscle relaxation and classical music can be used as an alternative to reduce menstrual pain (dysmenorrhea).